Kinematic differences between female national and provincial athletes in the tennis serve - Chen, Yan; Wang, Tianyang; Zhao, Yuyan; Zhan, Genghao; Tang, Yinchao; Wang, Zefeng (PeerJ, 2024)
Background Tennis, the second-largest ball game in the world, has a particularly wide audience. To date, little research has been conducted on the biomechanics of female serves. Purpose The purpose of this study was to capture the key moments by using 1,000 frames/s high-speed video analysis, to analyze the kinematics of the serving techniques of national athletes and provincial athletes, to determine the differences between the two levels of athletes, and to provide theoretical references for the improvement of scientific training level. Methods Ten female athletes were selected as participants for this study, five of whom are national athletes, and the other are provincial athletes. Three-dimensional filming techniques were employed to capture videos of the first and second serve techniques. Simi Motion was applied to obtain the 3D kinematic data. Statistical analyses were performed using IBM SPSS Statistics 27.0, and Mann–Whitney U tests were conducted to determine differences between groups. Results Significant differences in kinematics were found between national and provincial athletes. At the moment of the left knee’s minimum flexion (T2), in the first serve, national athletes had a smaller shoulder-hip vertical plane angle (−18.281 ± 6.142° vs. −25.631 ± 3.497°; p = 0.047) and a larger hip vertical plane rotation angle (−9.378 ± 4.263° vs. −0.470 ± 4.724°; p = 0.047). In the second serve, national athletes had a smaller hip horizontal plane rotation angle (−1.720 ± 4.683° vs. 24.146 ± 24.014°; p = 0.047) but a larger hip vertical plane rotation angle (−11.553 ± 1.949° vs. −0.422 ± 4.958°; p = 0.009). At the moment of impact (T4), in the second serve, national athletes’ batting position (0.296 ± 0.088 m vs. 0.446 ± 0.094 m; p = 0.047) was further back. Additionally, in the second serve, national athletes consistently had their body center of gravity further back at T2 (−0.106 ± 0.052 m vs. −0.018 ± 0.048 m; p = 0.028), T3 (0.002 ± 0.038 m vs. 0.132 ± 0.039 m; p = 0.009), and T4 (0.073 ± 0.050 m vs. 0.217 ± 0.034 m; p = 0.009). Conclusions The results of this study indicated several significant kinematic differences between national and provincial athletes, these variations were noted in the shoulder, hip, and body center of gravity. In summary, for the overall first and second serves, it is recommended that national athletes increase the horizontal plane angle of the shoulders and hips at T2, whereas provincial athletes decrease the horizontal plane angle of the shoulder–hip. In addition, provincial athletes need to increase the vertical plane angle of the hip joint, so that the top of the hip can be increased more, and provincial athletes need to be careful not to have the center of gravity too far in front of the body at T2, T3, and T4, so that it can hit the ball at a higher position to increase the swing speed.
Keywords: Tennis serve; High-speed video analysis; Kinematics; Differences